Comparison Between Surfactant and Chitosan Organo-kaolin Adsorbents to Remove Metal and Organic Compound in Peat Water. Issue 1 (June 2019) - Syafruddin,; Putra, A; Hidayat, M S
Abstract: This study compares adsorbents to remove metal and organic compounds in peat water solution. The kaolin adsorbent was modified with organic compounds (organo-kaolin). Modifications used two types of organic compound namely surfactant and chitosan with the organic compound concentration used of 15%, 39% and 45% respectively from the total weight of 200 grams adsorbent. The contact time used was 30 minutes with stirring speed of 90 rpm. The concentration of metal ion Fe and organic compound was analyzed by Atomic Absorption Spectrometer (AAS) (Shimadzu UV-1800) and Total Organic Carbon (TOC), the determination of the characteristics for wavelengths before and after treatment used Spectrophotometer Fourier Transform Infra-Red (FTIR) IR Prestige-2, while organo-kaolin surface morphology used SEM. The results of the study show that organo-kaolin surfactant and chitosan successfully reduces Fe metal ion in water up to 91.8% and 88.2% of the initial concentration of 2.07 mg/L from peat water. Both organo-kaolin modification (surfactant and chitosan) ability to remove organic compound was 46.7% and 35.7%. The results of FTIR spectra testing and SEM test also show differences before and after the absorption of the metal ion Fe and organic compounds.